THE ALGORITHM OF FORMATION OF CONFLICTING SITUATIONS FOR FULL FLIGHT SIMULATOR - A. N. Akimov; A. F. Kulagin (Научный вестник МГТУ ГА)
An algorithm of formation of a conflicting situation for the Full Flight Simulator is described. The algorithm calculates the trajectory of the intruder that potentially can lead to the collision with "evading aircraft" - FFS. In case of near miss, traffic collision avoidance system (TCAS) triggers, after which the crew trains collision avoidance techniques.